2005
DOI: 10.1186/1476-511x-4-6
|View full text |Cite
|
Sign up to set email alerts
|

Human macrophages limit oxidation products in low density lipoprotein

Abstract: This study tested the hypothesis that human macrophages have the ability to modify oxidation products in LDL and oxidized LDL (oxLDL) via a cellular antioxidant defence system. While many studies have focused on macrophage LDL oxidation in atherosclerosis development, less attention has been given to the cellular antioxidant capacity of these cells.Compared to cell-free controls (6.2 ± 0.7 nmol/mg LDL), macrophages reduced TBARS to 4.42 ± 0.4 nmol/mg LDL after 24 h incubation with LDL (P = 0.022). After 2 h in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2005
2005
2023
2023

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 40 publications
0
6
0
Order By: Relevance
“…Previous studies have supported the positive predictive effect of GPx activity on circulating levels of ox-LDL [ 16 , 18 ]. Experimental studies showed an increase in the activity of this enzyme in endothelial cells or macrophages treated with ox-LDL, as a protective mechanism against the increased generation of reactive oxygen species induced by ox-LDL [ 17 , 18 ], while other observational study reported also a positive association between GPx activity and ox-LDL in healthy young Spanish adults, despite it was not statistically significant [ 16 ]. Thus, our findings are in agreement to the hypothesis that a positive association between GPx activity and ox-LDL might constitute a consequence of the high ox-LDL concentrations, being an adaptive mechanism to prevent further oxidative imbalance.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies have supported the positive predictive effect of GPx activity on circulating levels of ox-LDL [ 16 , 18 ]. Experimental studies showed an increase in the activity of this enzyme in endothelial cells or macrophages treated with ox-LDL, as a protective mechanism against the increased generation of reactive oxygen species induced by ox-LDL [ 17 , 18 ], while other observational study reported also a positive association between GPx activity and ox-LDL in healthy young Spanish adults, despite it was not statistically significant [ 16 ]. Thus, our findings are in agreement to the hypothesis that a positive association between GPx activity and ox-LDL might constitute a consequence of the high ox-LDL concentrations, being an adaptive mechanism to prevent further oxidative imbalance.…”
Section: Discussionmentioning
confidence: 99%
“…Overall, this study aimed to assess plasma ox-LDL concentrations and the potential associations with oxidative stress markers as well as with anthropometric and metabolic (glucose and lipid profiles) data in healthy young adults. Thus, we measured plasma uric acid concentrations and glutathione peroxidase (GPx) activity in erythrocytes, since an altered regulation of these markers has been associated with ox-LDL concentrations in oxidative stress and chronic disorders conditions [ 11 , 12 , 17 , 18 ]. Also, we also assessed nail levels of three trace elements related to antioxidant defense mechanisms (selenium, zinc and cooper), whose levels have presented relevant associations with biomarkers in young adults [ 13 , 14 , 19 ].…”
Section: Introductionmentioning
confidence: 99%
“…Thiobarbituric acid-reactive substances (TBARS) were determined as described 70 . Fluorescence was measured at 553 nm with 515 nm excitation.…”
Section: Methodsmentioning
confidence: 99%
“…Fluorescence was measured at 553 nm with 515 nm excitation. Levels of hydrogen peroxide equivalents (H 2 O 2eq ) were analyzed in cultured bone marrow–derived macrophages 70 . The assay is based on the oxidation of ferrous ions to ferric ions by hydrogen peroxide at acidic pH (OXIS International).…”
Section: Methodsmentioning
confidence: 99%
“…In brief, male WT were systemically treated with T-0681 (36 nmol/kg/d) or PBS for 14 days using Alzet micro-osmotic pumps as described above; the treatment was continued during the 48-h RCT study. J774 macrophages were grown in suspension using a CELLspin 500 (Integra Biosciences, Chur, Switzerland) and radiolabeled with 2.5 µCi/ml [ 3 H]-cholesterol (PerkinElmer, Boston, MA, USA) and 40 µg/ml acetylated LDL (AcLDL) [28] for 48 h. These foam cells were washed twice, equilibrated in medium with 0.2% bovine serum albumin for 6 h, spun down, and resuspended in PBS. The cholesterol content of J774 foam cells was markedly elevated, and the majority of cellular cholesterol was esterified (>80%), as determined by thin-layer chromatography.…”
Section: Methodsmentioning
confidence: 99%